2010
DOI: 10.1007/s13197-010-0197-8
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of chitosan as cryoprotectant on croaker fish (Johnius gangeticus) surimi during frozen storage

Abstract: Effect of chitosan on physicochemical attributes of croaker fish surimi during storage at −20±2°C for 180 days was evaluated. The quality of croaker surimi added with 1% (w/w) chitosan was examined in terms of muscle protein, thaw drip, gel strength and Ca 2+ ATPase activity comparing with those surimi samples added with 4% sucrose and 4% sorbitol. Surimi without any cryoprotectant was treated as control. Chitosan showed cryoprotective effect similar to commercial cryoprotectants as both of them minimized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Kaba, (2006) reported that the yield of anchovy was 22%. Dey and Dora, (2011) reported 32.90% yield of gangetic croaker surimi. In the present study, the yield of surimi value was comparable with the value reported by Dey and Dora, (2011) in gangetic croaker (32.90%).…”
Section: Results and Discussion Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaba, (2006) reported that the yield of anchovy was 22%. Dey and Dora, (2011) reported 32.90% yield of gangetic croaker surimi. In the present study, the yield of surimi value was comparable with the value reported by Dey and Dora, (2011) in gangetic croaker (32.90%).…”
Section: Results and Discussion Yieldmentioning
confidence: 99%
“…Dey and Dora, (2011) reported 32.90% yield of gangetic croaker surimi. In the present study, the yield of surimi value was comparable with the value reported by Dey and Dora, (2011) in gangetic croaker (32.90%). Although the surimi yield percentage in the present study was slightly higher than the yield rate as reported by Sharma, (1989).…”
Section: Results and Discussion Yieldmentioning
confidence: 99%
“…Moisture content decreased with advancing storage days while chitosan effectively maintained it for longer time. Chitosan coating may decrease the surface hydration, cell rupturing, and ice crystal formation (Dey & Dora, 2011). In the present study, data showed significant decrease in crude fat content with increasing storage days, however, the reduction rate was minimized by adding chitosan or rosemary.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation is obtained according to the original technology through maceration of animal endocrine raw materials, followed by purification, concentration, isolation and freeze dehydration of the enzyme complex. Protepsin is characterized by proteolytic activity, the level of which begins from 50 units/g at pH 5.5 (Dey & Dora, 2011). Protepsin is an enzyme preparation of animal origin, containing a complex of acidic proteinases, intended for use in the meat industry for processing raw meat.…”
Section: Introductionmentioning
confidence: 99%